Sparassis fanjingshanensis, a new species of Sparassidaceae from Fanjingshan National Nature Reserve in China - He, Rong-Jian; Yang, Hui; Wei, Chun-Mou; Feng, Li-Jian; Zhang, Zhi-Chang; Gu, Chang-Hua (Phytotaxa, 2024)
Sparassis fanjingshanensis is described as a new species of Sparassidaceae based on morphology and phylogenetic analyses in this study. It was found in Abies fanjingshanensis community of the massy dwarf forest to Fanjing Mountain, China, and this is the only site of its occurrence known to date. Phylogenetic analysis of the sequences based on the internal transcribed spacer (ITS), the nuclear ribosomal large subunit (LSU) and partial gene coding RNA polymerase subunit II (rpb2) indicated that Sparassis fanjingshanensis belonged to the genus Sparassis and it formed a novel monophyletic clade next to Sparassis subalpina. Sparassis fanjingshanensis can be distinctly distinguished by its large basidiomata and light-gray to light-khaki flabellae that is compactly arranged, entire, broadly spathulate, slightly contorted, surface glabrous, top margin undulate, smooth, stem with concentric ring ornamentation (similar to the annual rings of a tree). In total, up to now, four taxa have been found in East Asia: Sparassis cystidiosa f. labelliformis, Sparassis fanjingshanensis, Sparassis labelliformis and Sparassis subalpine.